A simplified ground thermal response model for analyzing solar-assisted ground source heat pump systems. (1st June 2018) - Fine, Jamie P.; Nguyen, Hiep V.; Friedman, Jacob; Leong, Wey H.; Dworkin, Seth B.
Highlights: A solar-assisted ground source heat pump system is analyzed for three buildings. A simplified ground thermal model is developed to estimate ground thermal response. Compute times can be reduced by using the simplified ground thermal model. Ground thermal balance and system performance were determined for each building. An economically optimal quantity of solar panels can exist for buildings. Abstract: Ground source heat pump systems that are installed in areas with heating or cooling dominant seasons, or in buildings with utilization characteristics that lead to a disparity in demand, often encounter challenges related to ground thermal imbalance. This imbalance can lead to long-term ground temperature changes and may cause premature system failure. This paper focuses on combining a ground source heat pump system with a solar thermal array, with the goal of eliminating the effect of ground thermal imbalance, and minimizing system lifetime cost. A thermal mass ground heat transfer model is combined with a time-stepping model to analyze the system for a variety of solar array sizes. The details associated with this modelling technique are presented, and case studies are provided to illustrate the results of the calculations for three different buildings. It is shown that increasing the solar array size can offset ground thermal imbalances, but increasing the array size also results in a larger initial system cost. An economic analysis is then carried out to determine the system lifetime cost as a function of this solar array size, and an optimal array size from an economic perspective was found. The result of the study shows that hybridizing a ground source heat pump system with a solar array produces a viable system from a technical and economic standpoint, can be used to avoid premature system failure, and can reduce system lifetime cost.